Wykorzystanie miary Hamanna do oceny podobieństwa modeli w podejściu wielomodelowym - Gatnar, Eugeniusz (The use of Hamann's coefficient as diversity measure in multiple-model approach, 2006)
Combining multiple classifiers into an ensemble has proved to be very successful in the past decade. The key issue is the diversity of the component classifiers, because unrelated members form an accurate ensemble. In this paper we propose a new pairwise measure of diversity for classifier ensembles based on Hamann's similarity coefficient.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (13); 2006; nr 1126, s. 56-64